Analysis of Economic Cost of Secondary Level Education in Nepal - Pandey, Baikuntha (Patan Prospective Journal, 2022)
Investing on educations seeks a large span of time to get its return. Investment on education is the prime factor for transformation of a society. Educational cost is a measure of what a student, an institution of learning, or the public must give up educating an individual or a group of people. The opportunity cost represents the sacrifice of alternative opportunities to use the resource, either for present consumption or for some other forms of investment. The educational system uses up other resources which have alternative uses, even though these are not reflected in normal expenditure on education. The most obvious example of the opportunity cost is the time of students, who deprive the labour market of their services by choosing to continue their education. This represents a loss of current output for the economy, as well as a loss of earnings for the individual. There are, of course, considerable problems involved in measuring the opportunity cost of students. It is also worth emphasizing that estimates of opportunity costs make sense only within a given institutional framework. The concept of opportunity cost and the technique of cost-benefit analysis are not, however, applicable to situations where a total change in the entire educational or economic structure is contemplated. Better educated population relates to lower expenditures in other public sectors: e.g., better educated people tend to use health system less often since they would possess more information and knowledge on sickness prevention, if faced with unemployment they tend to stay unemployed for shorter periods of time thus relying less on welfare support etc. Per unit cost been assessed NRs 30,000/-which comprises unit cost+ average drop-out cost+ direct cost of guardians.Opportunity cost is assessed NRs.58,333/-and total education cost is assessed NRs 88,333/- i.e., $803. The net return from education must exceed NRs 88,333/-.